Introspection and Reflections on The Plague Through Literary Works Mustofa Bisri and Risda Nur Widia: Introspeksi dan Refleksi Menyoal Wabah Melalui karya Sastra Mustofa Bisri dan Risda Nur Widia - Saptawuryandari, Nurweni (Balai Bahasa Provinsi Papua, 2023)
Disasters in the formof plagues or pandemics, for example in human life, are problems that are not easily accepted because they cause worry and anxiety. The outbreak of the Covid-19 pandemic throughout the universe in the world, including Indonesia, has also caused endless anxiety and worry. Various print and electronic mass media discussed the pandemic, including Indonesian literati. Related to that, the discourse of plague became a realm to be explored in the creative space of the creation of literary works, in this case short stories. Mustofa Bisri or Gus Mus and Risda Nur Widia wrote a short story entitled